Gender and Climate Smart Agriculture in Rice Farming in Ikwo Local Government Area, Ebonyi State, Nigeria - Ovuoba , M.N.; Onyeneke, R.U.; Osuji, E.E. (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The paper conducted gender analysis of adoption of climate smart agriculture (CSA) in rice farming in Ikwo Local Government Area, Ebonyi State, Nigeria. Cross sectional data from 120 rice farmers (60 male and 60 female rice farmers) were collected. Data collected were analyzed using descriptive statistics. The results showed that the male rice farmers had more access to improved seedlings, and tractor/machinery relative to the female rice farmers. The male rice farmers performed more roles in terms of nursery practices, fertilizer and pesticide applications, while the female rice farmers did more of rice planting, weeding, harvesting, threshing and parboiling. Male rice farmers adopted more of knowledge smart practices, information smart practices, nutrient smart practices, and water smart practices, than female farmers. The study recommends farmers to plan their yearly rice cultivation in line with accessed climate change information and effectively adopt CSA practices and techniques to avert adverse climate changes in the state.